INTEGRATING FACTORS

µ ( x , y ) M ( x , y )dx + µ ( x , y ) N ( x , y )dy = 0

If the DE M ( x , y ) dx + N ( x , y ) dy = 0 …….(1) is not exact but when multiplied by a factor µ ( x , y ) and the resulting equation is exact thenµ ( x , y ) is called an integrating factor of the DE (1). Following are the guidelines / Rules for finding the integrating factor:My − Nx a. If eq (1) is not exact and =P where P is a function of x only. N Then eq (1) has an integrating factor (I.F) µ ( x ) µ(Is)solution of x which also depends on x.

dµ dµ = Pµ ⇒ = Pdx dx µ

⇒ µ ( x) = e

∫ pdx

b. If equation (1) is not exact and N x − M y =Q M where Q is a function of y only. Then eq (1) has an integrating factor µ ( y ) which also depends on y. is solution of dµ dµ = Qµ ⇒ = Qdy dy µ

µ( y)

⇒ µ ( y) = e
xM + yN ≠ 0

∫ Qdy

c. If eq (1) is homogeneous 1 then is the I.F of eq (1)

and

xM + yN

d. If eq (1) isyN the 0 xM − of ≠ form and then

yf ( x , y )dx + xf ( x , y )dy = 0

1 xM − yN

is the IF

e. When the DE

x y ( yAdx + xBdy ) = 0
a b

(a, b, A and B being constants) Is not exact, then

(x

kA −1− a

y

kB −1− b

)

is an integrating factor of the DE where K is any constant whose value is to be = 0 xdy − ydx determined., Example The eq is not exact. 1 But if we multiply it by DE and its solution is

x it becomes an exact xdy − ydx y y = 0 ⇒ d{ } = 0 ⇒ = c 2 x x x

2

Note: The number of I F of an eq may be infinite. The following differential formulas are useful in the calculation of certain Exact equation by inspection or Regrouping. 1. xdy + ydx = d ( xy ) 2. 3. 4.

1 2 1 2 2 2 xdy + ydx = d [ ( x ± y )] = d ( x ± y ) 2 2 xdy − ydx y = d[ ] 2 x x xdy − ydx x x = d [− ] = − d [ ] 2 y y y

5. 6.

xdy − ydx y = d [ln ] xy x xdy − ydx −1 y = d [tan { }] 2 2 x +y x xdy − ydx 1 x+ y = d[ { }] 2 2 x −y 2 x− y y = d [sin { }] 2 2 x x x −y
−1

7.

8.

xdy − ydx

9.

dx + dy = d [ln( x + y )] x+ y xdy + ydx 1 = d [− ] 2 2 x y xy ydx − xdy 1 x− y = d[ { }] 2 ( x + y) 2 x+ y xdy − ydx 1 x+ y = d[ { }] 2 ( x − y) 2 x− y

10.

11.

12.

Solve (1) Soln:

(4 x + 3 y )dx + 2 xydy = 0
2 2

………

Here....M = 4 x + 3 y ....N = 2 xy

∂M ∂N ⇒ = 6 y ..and ... = 2y ∂y ∂x ∂M ∂N ⇒ ≠ ..so eq is not exact ∂y ∂x ∂M ∂N − ∂y ∂x 6 y − 2 y 2 ⇒ = = N 2 xy x (a function of x alone) dx

IF = e

2

x

=e

2 ln x

=e

ln x 2

=x

2

Multiply eq (1) by IF x 2 , we obtain

(4 x + 3 x y )dx + 2 x ydy = 0
3 2 2 3 3 2 2

………..(2)
3

Now...M = 4 x + 3 x y ..and.. N = 2 x y
∂M ∂N 2 ⇒ = 6x y ..and ... = 6x 2 y ∂y ∂x Eq (2) become exact, therefore soln is
y = constant

Mdx + =c

Free from x

Ndy = c

⇒ (4 x + 3 x y )dx +
3 2 2 y = constant

Free from x

∫ 0dy

⇒ x4 + x3 y2 = c

Solve

xdy − ydx = ( x + y )dx
2 2

Soln: The given eq may be written as

xdy − ydx 2 xdy − ydx x = dx ⇒ = dx 2 2 2 2 x +y x +y 2 x xdy − ydx 2 x ⇒ = dx 2  y 1+    x

y ⇒ d [tan { − }] = dx x
−1

Integrate it

y ⇒ tan { − } = x + c x y ⇒ = tan( x + c) x
−1

⇒ y = x tan( x + c)

Solve (1)

( 2 xy + y )dx − x dy = 0
2 2

………
2

Soln: ∂M ∂N ⇒ = 2 x + 2 y ..and ... = −2x ∂y ∂x ∂M ∂N ⇒ ≠ ..so eq is not exact ∂y ∂x ∂N ∂ M − − 2x − 2 y − 2 y − 2x − 4 y ∂x ∂y ⇒ = = 2 M y + 2 xy y( y + 2 x )

Here....M = 2 xy + y ....N = − x
2

− 2( y + 2 x ) − 2 = = y( y + 2 x ) y

(a function of y alone)

∫ g ( y )dy = e ∫ IF = e
−2

dy y

=e

− 2 ln y

=e

ln y − 2

1 Multiply eq (1) by IF 2 , we obtain y

1 = y = 2 y
−2

2x x dy (1 + )dx − 2 = 0 y y

2

………..(2)
2

2x x Now..M = 1 + ..and.. N = − 2 y y
∂M 2x ∂N 2x ⇒ =− ..and ... =− ∂y y ∂x y
Eq (2) become exact

Therefore soln is

y = constant

∫ Mdx + ∫ Ndy = c
Free from x

2x ⇒ (1 + )dx + 0dy = c y Free from x

y = constant 2

x ⇒ x+ =c y

dy dy y− x = x+ y dx dx dy Soln: y − x = ( x + y) dx ( y − x )dx − ( x + y )dy = 0
Solve Here M = y-x and N = -(x+y)
∂M ∂N ⇒ = 1..and ... = -1 ∂y ∂x
2 2 2

eq is not exact

Mx + Ny = xy − x − xy − y = − ( x + y ) 1 IF = − 2 2 (x + y )
2

1 − 2 [( y − x )dx − ( x + y )dy ] = 0 2 (x + y )  y − x)   x+ y   2  x + y 2 dx −  x 2 + y 2 dy = 0         x+ y  ydx xdx − 2 − 2 2 2 2  x + y 2 dy = 0  x +y x +y   ydx − 2 2 x +y

⇒ ⇒

⇒ ∫ Mdx = ∫
y.constant

xdx 2 2 x +y

⇒ ∫ ⇒ ∫

1 [ ]dx 1 y Mdx = −[ 2 x 2 y = constant [ 2 ]+ 1 y

2 xdx ] 2 2 x +y

x 1 2 2 Mdx = tan [ ] − ln( x + y ) y 2 y = constant
−1

⇒ ∫
Now

x 2 2 Mdx = tan [ ] − ln ( x + y ) y y = constant
−1

Free from x

∫ Ndy = ∫ o.dy = c

The solution is

y = constant

Mdx +

Free from x

Ndy = c

x 1 2 2 tan [ ] − ln( x + y ) = c y 2
−1

Solve Soln:

y( xy + 2 x y )dx + x( xy − x y )dy = 0
2 2 2 2

( xy + 2 x y )dx + ( x y − x y )dy = 0
2 2 3 2 3 2 2 2 3 2 3 2

Here .. M = ( xy + 2 x y )
∂M ∂N 2 2 2 2 ⇒ = 2 xy + 6 x y ..and ... = 2 xy − 3 x y ∂y ∂x
eq is not exact, so
2 2 3 3 2 2 3 3

and .. N = ( x y − x y )

Mx − Ny = x y + 2 x y − x y + x y = 3x y ≠ 0
3 3

⇒ ⇒

1 IF = 3 3 3x y 1 2 2 3 ( xy + 2 x y )dx 3 3 3x y 1 2 3 2 + 3 3 ( x y − x y )dy = 0 3x y 1 2 1 1 ( 2 + )dx + ( 2 − )dy = 0 x y x x y y

dx dy 2dx dy ⇒ 2 + 2 + − =0 x y x y x y ydx + xdy 2dx dy ⇒ + − =0 2 2 x y x y 2dx dy ⇒ ( xy ) d ( xy ) + − =0 x y
−2

On integration, we get

−1 + 2 ln x − ln y = c xy

−1 x ⇒ + ln =c xy y
2

Solve Soln:

( 3 y + 4 xy )dx + ( 2 x + 3 x y )dy = 0
2 2

3 ydx + 4 xy dx + 2 xdy + 3 x ydy = 0
2 2

⇒ ⇒ ⇒ ⇒ ⇒

4 xy dx + 2 xdy + 3 ydx + 3 x ydy = 0
2 2

x(4 y dx + 2dy) + y( 3dx + 3 x dy) = 0
2 2

x y (4 y dx + 2dy) + x y ( 3dx + 3 x dy) = 0
1 0 2 0 1 2

Eq-I + Eq-II=0 Solving eq-I, a=1, b=0, A=4 and B=2 IF x kA− 1− a y kB− 1− b = x 4 k − 1− 1 y 2 k − 1− 0 = x 4 k − 2 y 2 k − 1

Solving eq-II, a=0, b=1, A=3 and B=3 so IF is

x

k1 A − 1 − a

y

k1 B − 1− b

=x

3 k1 − 1 − 0

y

3 k1 − 1 − 1

=x

3 k1 − 1

y

3 k1 − 2

Now And

4k − 2 = 3k1 − 1 ⇒ 4k − 3k1 = 1...(i ) 2k − 1 = 3k1 − 2 ⇒ 2k − 3k1 = − 1...(ii ) k = 1 = k1 =x y
2

Solving eq (i) and eq (ii), we get So IF

x 2 y( 3 y + 4 xy 2 )dx + x 2 y( 2 x + 3 x 2 y )dy = 0

( 3 x 2 y 2 + 4 x 3 y 3 )dx + ( 2 x 3 y + 3 x 4 y 2 )dy = 0
2

⇒ M = (3 x ⇒

y + 4 x y )..and .. N = ( 2 x y + 3 x y )
2 3 3 3 4 2

∂M ∂N 2 3 2 = 6 x y + 12 x y ..and .. = 6 x 2 y + 12 x 3 y 2 ∂y ∂x
eq is exact So solution is
2 2

y = constant

Mdx +
3

Free from x

Ndy = c

⇒ ∫ (3 x ⇒ xy
3

y + 4 x y )dx + 0.dy = c
3

2

+ x4 y3 = c

Solve

( y − 4 y )dx + ( x + x y )dy = 0
2 2 2

Solve

e dx + (e cot y + 2 y csc y )dy = 0
x x